Standardization of Seed Germination Aspects in Asparagus racemosus Willd. and Sida cordifolia Linn. in Arid Region of India - VANDANA VERMA; PAWAN K. KASERA (Seed Research, 2026)
Asparagus racemosus and Sida cordifolia are considered to be the most important medicinal plants of the Indian Thar desert. The present paper deals with seed germination studies of these plants under in vitro and in vivo conditions. Seed morphology, imbibition, germination (under different light regimes, growth regulators, acid and mechanical scarifications), vigour index, seedling quality index, sowing depth and soil mixture ratios experiments were conducted on these plants. Results revealed that seeds of A. racemosus exhibit 100% germination under controlled conditions, while those of S. cordifolia require conc. H₂SO₄ scarification for 15 min for maximum germination percentage. Maximum seedling quality index was obtained when the seeds were sown at D₂ (1.0 cm) depth with R₁ (1:1:1) soil mixture ratios of sand: clay: FYM in A. racemosus, while at D₁ (0.5 cmydepth in R3 (2:2:1) ratio in S. cordifolia.